A New Blood Glucose Control Scheme for Unannounced Exercise in Type 1 Diabetic Subjects - Beneyto, Aleix; Bertachi, Arthur; Bondia, Jorge; Vehi, Josep (IEEE transactions on control systems technology, 2020)
The artificial pancreas (AP) system or closed-loop blood glucose (BG) regulation is a technological advancement that aims to relieve diabetic subjects from their current decisionmaking burden while tightening their BG levels. However, large disturbances such as meals and exercise still pose great challenges to a fully closed-loop system. In this paper, the problem of BG regulation with unannounced physical activity for type 1 diabetic subjects is addressed. We use a coordinated control strategy with insulin infusion and extra carbohydrates (CHO) for hypoglycemia avoidance. The insulin algorithm is based on a proportional-derivative controller with insulin feedback and the so-called safety auxiliary feedback element (SAFE) layer, and the algorithm for CHO is based on a predictive, quantified proportional-derivative controller. The UVa/Padua simulator glucose-insulin model is modified to include the effects of physical activity and is used to test the new AP. We consider scenarios where the subject does not announce physical activity and with challenging meals. Then, we analyze the performance and robustness of the combined insulin and CHO recommender system and compare them to the insulin-only controller. The simulation results show that the new AP system is able to mitigate daily hypoglycemia episodes (0.9 versus 0.2, p <; 0.01) and increase the time in range during day (91.5% versus 92.4%, p <; 0.01) without increasing the time above 180 mg/dl (6.3% versus 6.4%, p > 0.05).